ANALYSIS OF MUDSKIPPER (Periophthalmodonschlosseri) CHEMICAL CONTENT IN DIFFERENT STEAMING TEMPERATURES - Esfi Girsang; Edison Edison; Rahman Karnila (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The objective of the study was to examine the effect of varied steaming temperatures on the chemical composition of the fish flour (Periophthalmodonschlosseri). The method used was experimental and composed as Completely Randomized Design (CRD) by conducting the treatment of steaming the fish at different temperatures (60, 70, and 80 oC). The parameters assessed were the rendemen and the psycho-chemical characteristic of the fish flour. The results showed that nutrient proximate composition in fresh fish meat the dry based content of water 79.13% protein 92.83%, ash 4.54%, fat 1.13%, and carbohydrates1.50%. Steaming temperature 60oC was showing the best treatment, indicatedby yielded rendement 17.34%, the content of water 9.97%, protein 82.93%, fat 1.34% and ash 318%. The treatment of different steaming temperatures conducted was not affecting significantly to the physical appearance of fish flour, indicated by the similar aroma and texture characterized as brownish yellow color. The higher the temperature used, the darker the flour yielded color. Keywords: Mudskipper, flour, temperature, steaming